Перспективы развития электронной промышленности в Украине - Передерий, С.Л. (Економіка промисловості, 2012)
Рассмотрены основные тенденции и факторы, определяющие перспективы развития электронной промышленности Украины, предложен организационно-экономический механизм инновационного развития электронной промышленности на отраслевом, региональном уровне и уровне предприятия. Ключевые слова: электронная промышленность, организационно-экономический механизм, инновационное развитие. Розглянуто основні тенденції та фактори, що визначають перспективи розвитку електронної промисловості України, запропоновано організаційно-економічний механізм інноваційного розвитку електронної промисловості на галузевому, регіональному рівні та рівні підприємства. Ключові слова: електронна промисловість, організаційно-економічний механізм, інноваційний розвиток. The paper reviews the basic trends and factors which determine the prospects for developing the electronic industry in Ukraine: positive trends in the development of production potential, international integration and cooperation, capacity of consumer electronics market, rawmaterial, technological and production base for creation of chemically pure materials for electronics, educational potential, scientific potential. The author offers the organizational and economic mechanism of innovation-based development of Ukraine’s electronic industry that includes the following: working out of the strategy and national program for developing the electronic industry in Ukraine, defining the enterprises–points of growth, creation of associations and clusters in the electronic industry in order to increase scientific and technological provision for design and production of electronic products and their delivery on the internal and foreign markets, creation of educational and research centres under regional centres of innovation-based development, development of technologies transfer mechanism. Keywords: electronic industry, organizational and economic mechanism, innovation-based development.